Detection of Cross-Line Successive Faults in Non-Effective Neutral Grounding Distribution Networks - Yuxuan Jin; Bin Wang; Mingming Xu; Ruirui Xie; Zhi Li; Xuan Dong (Energies)
In a non-effectively grounded neutral point distribution network, prolonged feeder operation reduces the insulation level, thereby increasing the likelihood of single-phase grounding faults that can generate over-voltages and eventually lead to successive two-point grounding faults. Existing detection methods for single-phase grounding faults fail to identify the second grounding fault in such scenarios. This paper derives the steady-state analytical expressions for the electrical quantities during faults and examines the characteristic differences at various stages of successive grounding faults under different fault phase sequences. Based on these distinctive features, the paper proposes a detection method for successive cross-line grounding faults with varying fault phases. The effectiveness of the proposed algorithm is verified through both simulation and field data.